ASSESSMENT OF EFFICACY AND SAFETY OF COMBINED MICROINVASIVE LASER-SURGICAL TREATMENT OF RHEGMATOGENOUS RETINAL DETACHMENT - A.V. DOGA; D.O. SHKVORCHENKO; L.A. KRYL; M.R. TAEVERE (Паёми Сино, 2020)
Objective: To evaluate the efficacy and safety of combined laser-surgical treatment of rhegmatogenous retinal detachment (RRD).